An EMG analysis: seoi-nage in elite women's judo lightweight class - In situations of opposite grip - Imamura, R. T.; Iteya, M.; Parker, D. L. (Association for the Scientific Studies on Judo, Kodokan, 2017)
The measurement of the muscular output, and results of the awareness survey during the kenkayotsu Situation inidicated that, all three subjects recorded the highest muscular output, in kake phase of the throw. For powerful throw, more output, can be expected in the kuzushi and tsukuri phase of the throw. Each subject recorded unique muscular output, during each phase of the throw. Subject A in the kenkayotsu Seoi-Nage Situation primarily had upper body muscular output.; however the finish of the throw recorded significant output, from the lower limbs. A difference in skill level was observed compared to Seoi-Nage in aiyotsu situation. Subject B`s kenkayotsu Seoi-Nage starts with output, from t.he lower limb muscle group; output, from the upper limbs is aclded as the throw progresses. High muscular output, was recorded and little difference was observed compared to aiyot.su Situation. More focus on the upper limb muscles may be the key to improving technique. Subject. C`s kenkayotsu Seoi- Nage was primarily executed with upper limb muscles and core. A conscious effort to increase the output, of each muscle group may be the key to improving the Seoi-Nage technique.